Towards conflict resolution and collaborative consensus-making: a participatory approach to architecture design in the Nottingham Natural History Museum, Wollaton Hall - Zhang, Licheng (2016)
Public engagement in museum design has been widely discussed and practiced. Public engagement not only inspires the participants’ interests and creativity, but also significantly increases the communication between the museum and participants. To date, however, most museum engagement projects have only focused on the exhibition design, while very few projects try to discuss public participation in the architecture design of museum. Therefore, this thesis sets out to find the most appropriate way that members of the public can participate in the architecture design of a museum.